FRANCHISE PROMOTION FEATURES: HOW TO STAND OUT IN A SATURATED MARKET - Mamatkulova Shoira Jalolovna (Web of Journals Publishing, 2024)
In a highly competitive franchising market, successful franchise promotion requires unique strategies and a clear understanding of the target audience. The article examines key aspects of franchise promotion, including building a strong brand, developing competitive advantages, adapting to local markets, and effectively using digital tools. It describes approaches that help franchisors stand out from the competition and attract potential franchisees. The article will be useful for both franchise owners and marketing specialists interested in expanding their business through franchising.
Keywords: franchise, franchise promotion, saturated market, competitive advantage, franchising, target audience, marketing strategies, localization, digital tools, attracting franchisees.